Evaluasi Program Bantuan Pembangunan Rumah Layak Huni (Baperlahu): Studi Pada Kabupaten Mesuji Tahun 2019 - Maharani Karin K; Eko Budi Sulistio; Ita Prihantika (Jurnal Administrativa, 2021)
The Livable of Housing Development Assistance Program (BAPERLAHU) is a government facility to independently support the implementation of proper housing construction in a healthy and safe environment. The implementation of the housing development assistance program requires community involvement to achieve its main goal, namely to provide habitable housing for low-income people (MBR), the elderly or with disabilities. The purpose of this research is to evaluate how the results of the implementation of the Assistance for the Construction of Livable Houses (BAPERLAHU) program in Mesuji Regency in 2019 and to find out what factors affect the implementation of the program. The research method uses qualitative research, the types of data used are primary and secondary data where data collection uses documentation, observation and interview techniques. The results of the study show that the evaluation of the Livable Housing Development program (BAPERLAHU) in Mesuji Regency in 2019 has been going quite well. In 2019 the Livable Housing Development Assistance (BAPERLAHU) program succeeded in completing 322 unfit for habitation houses (RTLH) in Mesuji Regency. However, there are several factors that affect the implementation of the program, such as the political atmosphere, limited funds allocated, the lack of Community Assistants (TPM), and lack of supervision by the Housing and Settlement Area Office of Mesuji Regency.